2021
DOI: 10.21203/rs.3.rs-147547/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal Variation of the Indoor Mycobiome in Daycare Centers

Abstract: Background: Children spend considerable time in daycare centers in parts of the world, and are exposed to the indoor micro- and mycobiomes of these facilities. The level of exposure to microorganisms varies within and between buildings, depending on occupancy, climate and season. In order to evaluate indoor air quality, and the effect of usage and seasonality, we investigate the spatiotemporal variation in the indoor mycobiomes of two daycare centers. We collected dust samples from different rooms throughout a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Interestingly, in our recent study on seasonality of the indoor mycobiome, the indoor environment was more influenced by the outdoor fungal diversity during summer and fall (10). Thus, as the citizen scientists in the present study sampled during early spring, we may have detected a stronger influence of indoor variables compared to e.g.…”
Section: Factors Influencing the Indoor Mycobiomementioning
confidence: 52%
See 4 more Smart Citations
“…Interestingly, in our recent study on seasonality of the indoor mycobiome, the indoor environment was more influenced by the outdoor fungal diversity during summer and fall (10). Thus, as the citizen scientists in the present study sampled during early spring, we may have detected a stronger influence of indoor variables compared to e.g.…”
Section: Factors Influencing the Indoor Mycobiomementioning
confidence: 52%
“…In line with this, it has previously been shown that the concentration of fungi in daycare centers is higher compared to homes (9). In several studies, the outdoor environment has been reported as the main source of indoor fungi (10)(11)(12)(13) due to the influx of spores through windows, entrances and the ventilation system. Hence, the vegetation and climate that structure the outdoor fungi will indirectly also structure the indoor mycobiome (11).…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations